The true blue scouts of Sugar Man Swamp - Appelt, Kathi, 1954- (Atheneum Books for Young Readers, 2013)
Twelve-year-old Chap Brayburn, ancient Sugar Man, and his raccoon-brother Swamp Scouts Bingo and J'miah try to save Bayou Tourterelle from feral pigs Clydine and Buzzie, greedy Sunny Boy Beaucoup, and world-class alligator wrestler and would-be land developer Jaeger Stitch.